Management Facilities and Infrastructure in Improving Quality Learning at Elementary School - Ade Saripah; Ida Tejawiani (Papanda Publisher, 2026)
Effective facilities and infrastructure management is critical for educational quality, yet many elementary schools in rural areas face significant resource constraints that impede optimal facility utilization. This study examines how Planning, Organizing, Actuating, and Controlling (POAC) management principles are implemented to optimize facilities and infrastructure in improving learning quality at two elementary schools with contrasting institutional characteristics. A qualitative descriptive case study was conducted at SDN Cinangsi (public) and MIS Sukamulya (foundation-based private) in Cianjur Regency, Indonesia. Data were collected through semi-structured interviews with principals, teachers, and students, systematic observations, and documentary analysis. Data analysis employed Miles and Huberman's interactive model with triangulation to ensure validity. Both schools implemented systematic POAC-based management despite resource limitations. Planning involved participatory needs assessment and strategic prioritization. Organization utilized adaptive strategies including manual inventory systems with practical solutions. Implementation emphasized teacher creativity in developing improvised instructional materials. Supervision focused on administrative compliance but inadequately assessed pedagogical impact. Systematic facilities management through POAC principles, combined with stakeholder collaboration and teacher improvisation, enables resource-constrained schools to optimize facility utilization and support learning quality. However, supervision systems require enhancement to evaluate facility impacts on educational outcomes effectively.